Drying and Rainfall Shape the Structure and Functioning of Nitrifying Microbial Communities in Riverbed Sediments - Arce, Maria Isabel; von Schiller, Daniel; Bengtsson, Mia M.; Hinze, Christian; Jung, Hoseung; Alves, Ricardo J. Eloy; Urich, Tim; Singer, Gabriel (Frontiers in Microbiology, 2018)
Non-flow periods in fluvial ecosystems are a global phenomenon. Streambed drying and rewetting by sporadic rainfalls could drive considerable changes in the microbial communities that govern stream nitrogen (N) availability at different temporal and spatial scales. We performed a microcosm-based experiment to investigate how dry period duration (0, 3, 6 and 9 weeks) and magnitude of sporadic rewetting by rainfall (0, 4 and 21mm applied at end of dry period) affected stocks of N in riverbed sediments, their nitrifyingammonia-oxidizing bacteria (AOB) and archaea (AOA) microbial communities and rates of ammonia oxidation (AO), and emissions of nitrous oxide (N2O) to the atmosphere. While ammonium (NH4+) pool size decreased, nitrate (NO3-) pool size increased in sediments with progressive drying. Concomitantly, the relative and absolute abundance of nitrifying microbialAOB and, especially, AOA groups (assessed by 16S rRNA gene sequencing and quantitative PCR of ammonia monooxygenase genes, respectively) increased, despite an apparent decrease of AO rates with drying. An increase of N2O emissions occurred at early drying before substantially dropping until the end of the experiment. Strong rainfall of 21 mm increased AO rates and NH4+ in sediments, whereas modest rainfall of 4 mm triggered a notable increase of N2O fluxes. Interestingly, such responses were detected only after 6 and 9 weeks of drying. Our results demonstrate that progressive drying drives considerable changes in in-stream N cycling and the associated nitrifying microbial communities, and that sporadic rainfall can modulate these effects. Our findings are particularly relevant for N processing and transport in rivers with alternating dry and wet phases – a hydrological scenario expected to become more important in the future.